Mary Broadfoot Walker: 83 years since a historical discovery - Carvalho, Vitor Martinez de; Nogueira, Eduardo de Almeida Guimarães; Rosa, Gleysson Rodrigues; Fragoso, Yara Dadalti (Arquivos de Neuro-Psiquiatria, 2017)
Mary Broadfoot Walker was a Scottish physician who, in 1935, described in great detail the effect of an anticholinesterase drug (physostigmine) on the signs and symptoms of myasthenia gravis. An original five-minutes movie is available online and the skepticism of her contemporary British medical doctors is understandable when the drastic effect of the treatment is shown in this movie. What Mary Walker taught us, more than eight decades ago, about myasthenia gravis continues to be the basis of a pharmacological diagnostic test and treatment of this disease.
Keywords: myasthenia gravis; physostigmine; neostigmine; acetylcholinesterase